(untitled) (Bangladesh Journal of Neurosurgery, 2020)
Trigeminal schwannomas are rare tumors that are located in the posterior and middlecranial fossae in about a quarter of the cases. The presentation pattern is differentaccording to the involved compartment and the goal of surgery is complete removal.We present the case of a 28-years old man who presented with a left sided trigeminalschwannomas extending from the posterior to the middle fossa. Middle fossa part ofthe tumour was removed by extradural subtemporal approach and posterior fossapart was removed by retrosigmoidretromastoid approach Bang. J Neurosurgery 2020; 9(2): 162-167